Prevalence and characterisation of wounds in sheep attributed to attacks by kea (Nestor notabilis) on high country farms in New Zealand. Issue 2 (3rd March 2020) - Reid, CE; Gartrell, BD; Van Andel, M; Stafford, KJ; Minot, EO; McInnes, K
ABSTRACT: Aims: To characterise and classify wounds in sheep suspected to have been caused by attacks by kea ( Nestor notabilis ) (kea strike), and to report the prevalence of these wounds on five high country farms in the South Island of New Zealand. Methods: Data were collected from farms between 28 August 2012 and 20 September 2013. Sheep were examined opportunistically immediately after shearing for signs of wounds caused by kea. The age and sex of sheep were also recorded. Wounds were measured and characterised as recent, healing, or healed, and the estimated true prevalence was calculated for each farm. Results: Injuries consistent with kea strike wounds were identified in 70/13, 978 (0.5%) sheep examined. The estimated true prevalence varied between farms, from 0 (95% CI = 0–0.16) to 1.25 (95% CI = 0.97–1.61)%. Of the 76 wounds identified, 61 (80%) were located in the lumbar region, and 74 (97%) consisted of full-thickness ulceration of the skin, one showed evidence of injury to muscle and one to bone. The median length of the 63 wounds measured was 6 (min 1, max 23.5) cm, and 10/63 (13%) were categorised as recently healed, 47/63 (62%) as healing, and 17/63 (22%) as recent wounds. Conclusions: The results of this study show that kea strike on sheep was occurring at a low prevalence on the high country farms surveyed. The wounds identified were survivable, but the welfare impact of kea strike on sheep should be considered in balance with the conservation status of kea. There was clear variation in the prevalence of wounds attributed to kea strike between the farms but we were not able to identify the risk factors contributing to these differences. Future studies of kea strike should examine variables such as altitude, local kea density and distribution, and differences in kea strike management and husbandry practices, and should include high country farms without a history of kea strike.